Battles of the great commanders - Livesey, Anthony (London : Joseph, 1987)
"Twenty famous victories, won by some of the most outstanding field commanders in history, are ... portrayed in this ... book. Selected because of their vital contribution to the development of battlefield tactics, the commanders in this book span more than two thousand years of warfare ... The battles chosen reveal the vital links between the manner in which victory was achieved and the military skill and leadership of each great commander"--Jacket.
Alexander the Great : Battle of Gaugamela, 1 October 331 BC -- Scipio Africanus : Battle of Zama, October 202 BC -- Genghis Khan : Battle of the Indus, 24 November 1221 -- Henry V : Battle of Agincourt, 25 October 1415 -- Gonzalo de C?rdoba : Battle of the Garigliano, 29 December 1503 -- Gustavus Adolphus : Battle of L?tzen, 16 November 1632 -- Turenne : Battle of the Dunes, 14 June 1658 -- Marlborough : Battle of Oudenarde, 11 July 1705 -- Frederick the Great : Battle of Leuthen, 5 December 1757 -- George Washington : Battle of Princeton, 3 January 1777 -- Napoleon : Battle of Wagram, 5-6 July 1809 -- Wellington : Battle of Salamanca, 22 July 1812 -- Robert E. Lee : Battle of Chancellorsville, 1-6 May 1863 -- Allenby : Battle of Beersheba, 31 October-7 November 1917 -- Tomoyuki Yamashita : Battle of Singapore, 8-15 February 1942 -- Erwin Rommel : Battle of Gazala, 26 May-22 June 1942 -- Erich von Manstein : Third Battle of Kharkov, 20 February-18 March 1943 -- William Slim : Battle of Meiktila/Mandalay, 14 January-28 March 1945 -- Douglas MacArthur : the Inchon Landing, 15-29 September 1950 -- Moshe Dayan : the Sinai Campaign, 29 October-5 November 1956.
Includes bibliographical references (pages 196-197) and index.
Keywords: Armed Forces -- Biography; Armed Forces; Military forces -- Commanders - Biographies